How Does Quality Impact on Import Prices? - Konstantins Benkovskis; Julia Wörz (Oesterreichische Nationalbank (OeNB), 2011)
Understanding the dynamics of import price developments is an important but challenging issue which affects the way we look on consumers' welfare, real exchange rates and exchange rate pass-through. In this paper we propose an exact import price index which extends the approach by Broda and Weinstein (2006) who adjust price developments for changes in varieties of imported products. We relax two assumptions still underlying the Broda and Weinstein (2006) approach, thus allowing the set of imported goods and the quality to vary. This variety-, set-of-products-, and quality-adjusted import price index shows that gains from variety in European G7 countries, although positive, are rather small compared to calculated gains from quality. Using HS 07 (vegetables) as our benchmark group of products with unchanged quality, we find significant gains from quality for Germany, France, Italy and the UK between 1995 and 2010. Although these results are not invariant to the choice of the benchmark category, they clearly stress the importance of incorporating the quality issues in empirical literature. Ignoring changes in import quality can give misleading estimates of import prices and consumers' welfare.
Keywords: C43; D60; F12; F14; L15; 330; import variety; price index; quality; welfare gains from trade